2009
DOI: 10.1186/1756-9966-28-40
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor-1α correlates with vascular endothelial growth factor A and C indicating worse prognosis in clear cell renal cell carcinoma

Abstract: Background: The role of angiogenesis in the pathogenesis of renal cell carcinoma is well recognized, however, the influence of tumor cells in this activity has not yet been fully clarified. The aim of this study was to analyze the expression of hypoxia inducible factor-1α (HIF-1α), a regulatory factor of angiogenic switch, in comparison to vascular endothelial growth factor A and C (VEGF-A and VEGF-C), recognized to be involved in blood and lymph vessel neoangiogenesis, with potential association in the progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Several studies found VEGF-A overexpression as adverse prognostic marker [17, 24, 25], while others opted for VEGFR1 [17]. In summary, data are either controversial or missing on various HIFs and on HIF-regulated gene expressions as prognostic markers in ccRCC, especially regarding bone metastatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found VEGF-A overexpression as adverse prognostic marker [17, 24, 25], while others opted for VEGFR1 [17]. In summary, data are either controversial or missing on various HIFs and on HIF-regulated gene expressions as prognostic markers in ccRCC, especially regarding bone metastatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, previous studies have shown that HIF-1α expression is an adverse prognostic marker in ccRCC. 8,10,19,23,30 This is of particular interest since inactivation of the VHL tumor suppressor gene results in stabilization of the HIF-1α subunit. 16 Furthermore, HIF-1α is thought to downregulate the mTOR pathway independent of a hypoxic microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the definition of high HIF1α expression varied among studies, on average HIF1α protein was detected in 70% (range 17% to 97%) of ccRCC specimens. In a number of studies, HIF1α expression was associated with an inferior survival [55, 56, 61, 63]. Schultz et al [61] showed that HIF1α levels were significantly higher in primary and metastatic ccRCCs compared with benign tissues (P<0.0001), and that tumor size and HIF1α expression were independent predictors of both reduced disease free survival and tumor progression in primary ccRCC.…”
Section: Reviewmentioning
confidence: 99%